Pengaruh Pos Gizi Terhadap Pengetahuan Dan Pola Asuh Ibu Balita Di Wilayah Puskesmas Kwadungan Kecamatan Kwadungan Kabupaten Ngawi - Yudhawati, Ririn Madyaning, Muwakhidah, SKM., M.Kes, Fitriana Mustikaningrum, S.Gz., M.Sc (2016)
Introduction: Malnutrition has been the common problem that need serious solution. One of the causes of malnutrition among children is unappropriate feeding practices. Feeding can be influenced by the knowledge and parenting mothers. Positive Deviance is an approach to change behavior including the feeding of children, child care, hygiene, and child health care. Nutrition hearth centre is an application of the approach of Positive Deviance is a series of 12-day sessions designed to rehabilitate children who were severely malnourished and teach habits and Positive Deviant behavior using the knowledge and local resources available. Objective: The aim of study was to determine the effect of nutrition education centre mother's parenting in the Kwadungan.sub district heal center, Ngawi. Research Method: The quasi experimental design with pre and post test data was used in this study. The data of nutrition knowledge and parenting style according to breastfeeding, up bringing children, which is seen from how to give the children food, hygiene and medical health care Wilcoxon test was used as statistic analysis. Results:Better knowledge before and after test, according to 62,5% up to 87,5%. The same trend shows in parenting category which increase from 56,25% to 75%. Statistical analysis showed that there was significant effect of nutrition education center in knowledge and parenting styles with p<0.05 (p=0.000). Conclusion: The nutrition education center has positive impact in mother's education and parenting style.